Survey of antibodies to Peste des petits ruminants virus in small ruminants in the Mediterranean Region of Turkey - Şevik, M (Journal of the Hellenic Veterinary Medical Society, 2024)
Peste des petits ruminants (PPR) is a viral disease affecting sheep and goats caused by peste des petits ruminants virus (PPRV) has a serious economic impact due to the restrictions on animal trade and animal movements and high mortality rates in small ruminant populations. The common clinical sings of the PPR are fever, muco-purulent nasal discharge, diarrhoea and abortion. Seroepidemiological studies of PPRV infection in sheep and goats in Turkey are scant. Therefore, this study was aimed to evaluate the seroprevalence of PPR in small ruminants in Turkey. Ovine blood samples were collected by random sampling method from sheep (n = 77) and goats (n = 61) from unvaccinated flocks (n = 40) in the Antalya Province in the Mediterranean region of Turkey. A competitive enzyme-linked immunosorbent assay (c-ELISA) kit was used to detect antibodies against PPRV in sera samples. Out of 138 sera samples analysed, eighteen sera samples (13%, 95% CI: 7.4 - 18.7) were PPRV seropositive, of which 18.2% (95% CI: 9.6 - 26.8; 14/77) were from sheep, whereas 6.6% (95% CI: 0.3 - 12.8; 4/61) were from goats. Although PPRV seropositivity rate was higher in sheep than goats, it was not statistically significant (P = 0.07). PPRV seropositivity was higher in small ruminants older than 24 months (19.4%) compared with less than or equal to 24 months (7%) (P = 0.04). Although, there was no statistically significant difference between sexes, PPRV seropositivity rate was higher (14.5%) in females than males (10.9%) (P = 0.61). The flock-level seroprevalence was 30% (12/40). The result of the present study showed that seroprevalence of PPRV infection is high in sheep and goats in the Antalya Province. However, results of the study are not enough to determine the regional and country-based profile of the PPRV infection in Turkey. Further epidemiological studies are required to get more epidemiology data on PPR in Turkey.